Study on seismic performance of transverse frame of prefabricated elevated subway station. (August 2022) - Wei, Kelun; Xu, Yazhou; Li, Mingtao
Abstract: This paper presents an assembly scheme of double bridge column-elevated subway stations. The scheme can help to realize the assembly construction of urban elevated subway stations. A 1/6-scaled precast assembly transverse frame of elevated subway station was designed and fabricated to verify the scheme. The pseudo-static loading test was performed to investigate the bearing capacity, failure mode and hysteretic behavior of the precast assembly transverse frame. Test results showed no joint connection failure occurred during the test, and the test specimen had good ductility, indicating that the assembly scheme proposed in this paper was feasible. Finally, the finite element model was established by calling PQ-Fiber subroutine developed by Tsinghua University with ABAQUS to study the seismic performance of test specimen. And numerical simulation results were in good agreement with test results.